Development and evaluation of RT-qPCR assays for two neglected orthobunyaviruses: Oya virus and Ebinur Lake virus - Siyuan Liu; Wei Chen; Raphael Nyaruaba; Shunlong Wang; Cihan Yang; Qun Wu; Ying Liu; Puyu Liu; Fei Wang; Jingling Wang; Zhiming Yuan; Dingwei Sun; et al. (Virus Research, 2024)
Objectives: Oya virus (OYAV) and Ebinur lake virus (EBIV) belong to the genus Orthobunyavirus within the Peribunyaviridae family, and both are recognized as the novel virus with potential threat to the animal or public health. Given their potential to cause outbreaks and their detection in diverse samples across different regions, the need for a reliable and efficient molecular detection method for OYAV and EBIV becomes imperative. Methods: The S-segment of OYAV and EBIV was used for designing specific primer and probe sets, which were employed in a real-time reverse transcription quantitative PCR (RT-qPCR) assay. The analytical performance of these assays, encompassing specificity, sensitivity, reproducibility, and fitness for purpose, was thoroughly evaluated across various sample matrices. Results: The developed RT-qPCR assays were very specific to their respective targets. Both assays were highly reproducible (%CV<3) and sensitive with the 95% limit of detection (LOD) of 0.80 PFU/mL for OYAV primer probe set and 0.37 PFU/mL for EBIV primer probe set. Furthermore, the assays fitness for purpose was good as it could detect the specific viruses in virus-spiked serum samples, virus-inoculated mosquito samples, field caught mosquitoes and biting midge samples. Conclusions: Our study has successfully developed specific, sensitive, and reliable RT-qPCR assays for the detection of OYAV and EBIV. These assays hold great promise for their potential application in clinical and field samples in the future.